Flood risk typology analysis: Spatial distribution of river flooding and urban flooding as a foundation for disaster management planning - Arkha Dhemas Gunanda; Rachmadi Purwana; Triarko Nurlambang (ASEAN Natural Disaster Mitigation and Education Journal, 2026)
Background: Bantul Regency, Special Region of Yogyakarta, Indonesia, consistently experiences flood disasters with increasing frequency and economic losses, from IDR 1.2 billion in 2015 to IDR 7.1 billion in 2025, a nearly 500% increase. Despite possessing Disaster Risk Assessment (KRB) and Disaster Management Plan (RPB) documents compiled in accordance with national standards, the existing approach still treats flood risk homogeneously without differentiating between typologies with fundamentally different mechanisms and mitigation needs. Methods: This research employs a mixed-methods approach integrating GIS-based spatial analysis, document content analysis, and key informant interviews. Flood typology classification followed the framework of Bello et al. (2024), while risk component analysis applied the H×V/C formula per BNPB (2021) methodology. Spatial mapping used ArcGIS 10.3 with KRB DIY 2022 data, DIBI BNPB historical records, and BIG 2023 land cover data. Findings: Two fundamentally distinct flood typologies were identified riiver flooding concentrated in downstream Progo and Opak DAS areas, characterized by high hazard, medium-high vulnerability, and medium capacity; and urban flooding concentrated in Yogyakarta's urban buffer zones, characterized by medium-high hazard, high vulnerability from population and asset concentration, and medium infrastructure capacity. Both typologies produce high overall risk but with significantly different component profiles. The current KRB document does not explicitly classify flood typology and remains dominated by administrative boundary analysis rather than hydrological watershed units. Conclusion: Flood risk in Bantul Regency is not homogeneous. Typological differentiation carries concrete and distinct operational implications for each planning instrument. KRB methodology must be reoriented toward DAS hydrology-based analytical units with explicit typology classification as a prerequisite for effective and adaptive disaster management planning. Novelty/Originality of this article: This research introduces typology-based flood risk analysis as the fundamental unit of analysis in disaster management planning evaluation in Indonesia, integrating spatial GIS analysis with watershed hydrology approaches a methodological innovation not previously applied systematically in KRB evaluation at the district level.